2022
DOI: 10.1088/1361-6463/ac40ba
|View full text |Cite
|
Sign up to set email alerts
|

Capillary trees for passively pumping water

Abstract: Capillary flows are an attractive feature for passive water harvesting as they require no external driving force to pull the fluid out within the capillary network. Here we analyze the architecture of capillary flow networks in steady state, and the impact of the network morphology on the maximum mass flow rate that can be extracted for a fixed network volume and fixed network footprint. We develop a search algorithm to test the possible location of all the junction and bifurcation nodes and the changes in dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Such results are also supported by previous literature. 32,39,42 Furthermore, the capillary flow in the variable-diameter rootlike network is faster than that in equal-diameter root-like networks at 20 mm ≤ l ≤ 50 mm, because there is less viscous resistance in the variable-diameter network than the equaldiameter network with d 0 = d 1 = 0.05 mm and is subjected to higher capillary pressure than the equal-diameter network with d 0 = d 1 = 0.01 mm. Therefore, it is possible to obtain a faster capillary flow in root-like networks depending on the appropriate combination of structure parameters.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such results are also supported by previous literature. 32,39,42 Furthermore, the capillary flow in the variable-diameter rootlike network is faster than that in equal-diameter root-like networks at 20 mm ≤ l ≤ 50 mm, because there is less viscous resistance in the variable-diameter network than the equaldiameter network with d 0 = d 1 = 0.05 mm and is subjected to higher capillary pressure than the equal-diameter network with d 0 = d 1 = 0.01 mm. Therefore, it is possible to obtain a faster capillary flow in root-like networks depending on the appropriate combination of structure parameters.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Lee studied the effects of structural parameters on dewatering rate in artificial trees driven by capillary force and proposed that the increasing conduit diameter will enhance water flux. Recently, Zhang and Lorente , analyzed the capillary flow in steady state and obtained the maximum mass flow rate in root-like networks that are generated iteratively or randomly.…”
Section: Introductionmentioning
confidence: 99%
“…( 3)). Yet, our previous work 33 showed that in capillary networks the exponent γ in Eq. ( 3) diverges from the value 3 when the channels are in the vicinity of the network outlet.…”
Section: Liberating the Configurationmentioning
confidence: 98%
“…To study the effect of α apex on capillary flow, this study establishes several capillary channel models with wedge features given the same channel length and projection area [49]. The α apex is adjusted by changing the inlet and outlet widths as shown in table 4.…”
Section: Wedge-shaped Modelmentioning
confidence: 99%